The Sultan, Survivors, and Silencers: The #ArewaMeToo Movement in Northern Nigeria’s Online Sphere - Nasir, Muhammad Muhammad; Shamim, Saemah (Religió Jurnal Studi Agama-agama, 2024)
The #ArewaMeToo movement in Nigeria is a social media-driven campaign against sexual harassment and gender-based violence. The movement has generated controversy and resistance, prompting a closer examination of its emergence, trajectory, impact, and implications. This study, therefore, examines the emergence and trajectory of the movement and how it has used social media platforms such as Twitter (X) and Facebook to raise awareness about sexual harassment and gender-based violence in northern Nigeria. The movement has attracted significant attention and support, particularly from women who identify themselves as survivors of sexual harassment and who seek to challenge dominant approaches to sexual assault and harassment in the region. Drawing on both secondary and primary sources, this qualitative study provides a comprehensive understanding of the #ArewaMeToo movement and its impact. This research finds the controversial factors that contributed to the Nigerian Sultanate Council’s decision to ban the movement, including the influence of Muslim intellectuals and social media influencers. It also reveals the historical context, key actors, and impact of the movement, as well as the effectiveness of online movements in driving social change.